2006
DOI: 10.1080/02688690600999786
|View full text |Cite
|
Sign up to set email alerts
|

Free phenytoin concentration measurement in brain extracellular fluid: a pilot study

Abstract: We investigate the relationship between brain extracellular fluid free phenytoin concentration and plasma free phenytoin concentration in adults with acute brain injury. Daily cerebral microdialysate free phenytoin concentration was measured in eight adults with acute brain injury and compared to simultaneous measurement of plasma free phenytoin concentration.The group data revealed no significant correlation between microdialysate and plasma free phenytoin concentration (r=0.34, p=0.41). However in two patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…To our knowledge, our results for the antirejection drugs are novel, as no literature data on animals or humans are yet available to support these observations. On the contrary, a human study reported phenytoin levels in brain ECF, but found no correlation to phenytoin concentrations in blood 40. However, as the study did not specifically report phenytoin concentrations in ISF, it is unclear what fraction of drug found in ECF could be attributed to the interstitium.…”
Section: Discussionmentioning
confidence: 87%
“…To our knowledge, our results for the antirejection drugs are novel, as no literature data on animals or humans are yet available to support these observations. On the contrary, a human study reported phenytoin levels in brain ECF, but found no correlation to phenytoin concentrations in blood 40. However, as the study did not specifically report phenytoin concentrations in ISF, it is unclear what fraction of drug found in ECF could be attributed to the interstitium.…”
Section: Discussionmentioning
confidence: 87%
“…The steady-state extracellular phenytoin concentrations corresponded closely to the unbound plasma concentrations. Tisdall et al [83] also found a significant correlation between brain microdialysate and free plasma phenytoin concentration in two patients with acute brain injury. In an extensive study Rambeck et al compared brain extracellular fluid, brain tissue, cerebrospinal fluid and plasma concentrations of different AEDs measured intra-operatively in 22 pharmacoresistant epilepsy patients with complex partial seizures or secondary generalized seizures [84].…”
Section: Microdialysis and Biophase Kinetics Of Aeds In Epilepsymentioning
confidence: 87%
“…86 CMD could also help understand the role of brain cytokines, identify biomarkers, and help monitor intracerebral medication levels. [87][88][89][90][91] Ultimately, the use of CMD remains largely investigative, however it does provide the potential to understand cerebral metabolism, which confers different neurophysiologic data from the other aforementioned techniques.…”
Section: Cerebral Microdialysismentioning
confidence: 99%